Configuration- and concentration-dependent hybrid white light generation using red, green, and blue quantum dots embedded in DNA thin films. Issue 2 (17th October 2018) - Arasu, Velu; Jo, Deoksu; Chae, Heeyeop; Chung, Ho Kyoon; Park, Sung Ha
Abstract : A simple and hybrid white-light optoelectronic device with a single excitation source with efficient RGB colours on a stable optical platform was demonstrated. Abstract : Artificial white-light production from primary red, green, and blue (RGB) colours is in high demand in the lighting, information technology, and wearable display industries, and it requires a simple device structure and efficient templates with stable luminophores. To realize efficient and stable optoelectronic devices, relevant materials and device structures need to be identified. Therefore, we report the construction of a simple hybrid white-light optoelectronic device with a single excitation source with efficient RGB colours on a stable optical platform. Emission wavelength-tunable R, G, and B quantum dots (QDs) with specific ligands and cetyltrimethylammonium chloride (CTMA)-modified DNA (CDNA) are prepared for the fabrication of QDs embedded in CDNA thin films with mixed and orthogonally stacked configurations. Fourier transform infrared, photoluminescence quantum yield (PLQY), ultraviolet (UV)-vis absorbance, photoluminescence, and electroluminescence (excited by blue and UV LEDs) spectra of the QDs embedded in CDNA thin films are analyzed to investigate their ligand attachment, luminescence efficiency, optical excitation, spectral emission, and hybrid white-light properties. In addition, the dispersion and photostability of QDs in the CDNA matrix were analyzed. The colour rendering index (CRI) values and colour gamut of the QDs embedded in CDNA thin films are studied for evaluating the light quality. The results show that the ligands on the QDs enhance PLQY up to 95 and 25% in liquid and solid phases, respectively. The optical properties of the QDs in the CDNA thin films are not significantly affected by phase changes, which implies the effective hosting of QDs within CDNA. The CRI values of the mixed and stacked configuration-dependent QDs embedded in CDNA thin films are 21 and 80%, respectively, which suggest the relatively stronger self-absorption of R QDs in the mixed configuration than in the stacked configuration. In addition, CRI values and colour gamut are affected by different R, G, and B QD concentrations in CDNA. These findings are important for solid-state lighting, information display systems, flexible displays, and wearable displays.